Relationship between Self-Medication Practices and Patronage of Orthodox Medical Facilities among the Indigenous People of Yakurr Local Government Area, Cross River State, Nigeria - Etobe, Eteng Ikpi; Etobe, Utibe E. I.; Iniama, Joshua (Disease and Health Research: New Insights Vol. 3, 2024)
The study examines the relationship between self-medication and patronage of orthodox medical facilities in Yakurr Local Government Area, Cross River State, Nigeria. Three research objectives were drawn which guided the formulation of three null hypotheses from the independent variable. In spite of efforts put in by individuals, organizations and governments to curb the menace of self-medication, the practice is still on the increase. This is partly due to the absence of stringent government legislation and enforcement against over-the-counter drugs purchase and sales. The study adopted a descriptive survey design. A 17-item questionnaire entitled “Self-medication and Patronage of Orthodox Medical Facilities (SMPOMF)” were distributed to four hundred and forty-eight (448) respondents selected through simple random sampling techniques from the study area. In addition, key informants (KII) were used as data collection instruments. The reliability test of the instrument was conducted using the Cronbach reliability method. Data were gathered through primary and secondary sources and were analyzed using Pearson Product Moment Correlation Coefficient and One-way ANOVA statistical techniques. The three hypotheses, tested at 0.5 level of significance, revealed that there is a significant relationship between belief system, level of awareness (p=.337), proximity to the medical facility and self-medication in Yakurr Local Government Area, Cross River State, Nigeria (p=.325). This confirms that there is a significant relationship between self-medication and patronage of orthodox medical facilities in the study area. Relative to the phenomenon of self-medication ……. (No theory is first discussed, before criticism leveled against this theory), in seeking help the individual may take the wrong action by going to the chemist or patent vendor, for over-the-counter drugs, instead of going to qualified medical practitioners for examination, tests, diagnosis and treatments. The study recommends among other things, that, traditional medical practice should be integrated into the primary healthcare system to grant it a formal status in the healthcare delivery system in Nigeria. In addition, the safety and regulation of traditional medicine should be assessed to improve its standard and efficacy. In addition, the government ought to construct more healthcare facilities in the research region to entice residents to use them in the event of a medical emergency rather than turning to conventional medicine and, typically, ineffectual self-medication.